2021
DOI: 10.1002/alz.051317
|View full text |Cite
|
Sign up to set email alerts
|

The cerebrospinal fluid interleukin 8 (IL‐8) concentration in Alzheimer’s disease (AD)

Abstract: Background: Alzheimer disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia. The hallmarks underlying AD pathology are amyloid-β peptides, phosphorylated tau proteins and neuroinflammation. In vitro studies on cultured human microglia display a significant role of Interleukin 8 in neuroinflammation. Furthermore, CXCR2, IL-8 receptor, was found in dystrophic neurites which suggests connection to neuroinflammation in AD. Literature data indicates that gene polymorphism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…IL-1α plays a crucial role in AD pathogenesis, particularly the homozygosity for a specific IL-1α gene polymorphism at least triples the risk for the development of AD (reviewed in [ 44 ]). Again, studies in cultured human microglia display a significant role of interleukin-8 in neuroinflammation, and literature data indicate that gene polymorphism in IL-8 may affect the predisposition of AD [ 45 ]. Indeed, it has been demonstrated that micro vessels derived from AD brain express high levels of MIP-1α mRNA as well as release high levels of MIP-1α protein when compared with brain micro vessels isolated from cognitively healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1α plays a crucial role in AD pathogenesis, particularly the homozygosity for a specific IL-1α gene polymorphism at least triples the risk for the development of AD (reviewed in [ 44 ]). Again, studies in cultured human microglia display a significant role of interleukin-8 in neuroinflammation, and literature data indicate that gene polymorphism in IL-8 may affect the predisposition of AD [ 45 ]. Indeed, it has been demonstrated that micro vessels derived from AD brain express high levels of MIP-1α mRNA as well as release high levels of MIP-1α protein when compared with brain micro vessels isolated from cognitively healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 17, 2024. ; https://doi.org/10.1101/2024.06.14.599092 doi: bioRxiv preprint pathology. 56 These results suggested that stress response-related modules with HSPA5 in GPMNB+ activated microglia are drivers of the pathogenesis of AD and function by moderating Aβ-tau interactions in early-stage AD. These factors are potential biomarkers for early-stage AD.…”
Section: Discussionmentioning
confidence: 83%
“…This finding aligns with those of previous reports indicating that GPNMB expression is correlated with disease pathology. 56 These results suggested that stress response-related modules with HSPA5 in GPMNB+ activated microglia are drivers of the pathogenesis of AD and function by moderating Aβ-tau interactions in early-stage AD. These factors are potential biomarkers for early-stage AD.…”
Section: Discussionmentioning
confidence: 83%
“…Levels of TREM1, another microglial transmembrane protein, were also shown to increase in AD dementia compared with cognitively unimpaired controls and those with mild cognitive impairment (MCI) [14]. In addition, multiple interleukins (ILs) in CSF were associated with Aβ and tau pathology, as well as cognitive decline [15][16][17][18][19][20]. Similarly, several CSF markers of cerebrovascular integrity, such as sPDGFRB (soluble platelet-derived growth factor receptor β), ICAM1, VCAM1, and VEGFs, synaptic markers such as NPTX and NRGN, have been linked to AD and cognitive decline [18,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%